The Role of Brand Awareness in Shaping Customer Purchase Decisions: A Phenomenological Study of Nora Tex, a Muslim Fashion MSME in Indonesia - Nurus Sobakh (International Journal of Management, Accounting and Economics, 2025)
This phenomenological study explores how brand awareness influences customer purchase decisions in Nora Tex, a Muslim fashion micro, small, and medium enterprise (MSME) in Indonesia. By addressing a gap in literature on culturally embedded branding, the research delves into the emotional and religious dynamics driving consumer behavior in faith driven markets. Using a qualitative approach, data were collected from three key informants Nora Tex’s owner, an internal staff member, and a loyal customer through in-depth interviews, participant observation, and documentation. The analysis followed the Miles and Huberman framework, including data reduction, display, and conclusion drawing. The findings reveal that brand awareness not only operates through recognition but also through emotional connection and Islamic value alignment. Customers perceive Nora Tex as embodying modesty, trust, and religious identity, reinforcing brand loyalty. The study concludes that branding strategies in MSMEs can be strengthened through experiential consistency, culturally resonant messaging, and value-based engagement. These insights offer strategic implications for branding in religious and identity-based MSME contexts, highlighting the importance of aligning brand identity with cultural values to foster customer loyalty.